Trends and spatial patterns of human immunodeficiency virus prevalence among men and women aged 15–49 in Sierra Leone: evidence from the 2008, 2013 and 2019 Demographic and Health Surveys - Wei Ma; Augustus Osborne; Lovel Fornah; Mulugeta Shegaze Shimbre (BMJ Global Health)
Background Human immunodeficiency virus prevalence remains a major public health concern in Sierra Leone. This study examines the trends and spatial patterns of human immunodeficiency virus prevalence among men and women in Sierra Leone using data from the 2008, 2013, and 2019 Sierra Leone Demographic and Health Surveys (SLDHS).Method We analyzed data from three SLDHS conducted in 2008, 2013, and 2019. Men and women aged 15–49 who tested for HIV were eligible. A trend analysis was used to examine the change in human immunodeficiency virus prevalence. Spatial autocorrelation and Moran’s I statistic were used to assess the spatial distribution of human immunodeficiency virus prevalence. We used the 2019 SLDHS to determine the predictors of human immunodeficiency virus prevalence using geographically weighted regression.Results The study found that human immunodeficiency virus prevalence was 1.5% in 2008, 1.3% in 2013 and 1.7% in 2019. From 2008 to 2019, human immunodeficiency virus prevalence in the Western and Northwest regions increased, with a consistent rise in the Southern region and an increase in the Northern regions. We identified hotspots for human immunodeficiency virus prevalence in Koinadugu, Kono, Bo and Kailahun districts. In 2008 and 2013, the Kono district had the highest human immunodeficiency virus prevalence, while the western areas, Port Loko and Bombali districts had the highest risk in 2019. Our geographically weighted regression analysis indicated that, age 15–19, urban residence and no formal education were predictors of HIV prevalence in 2019.Conclusion The human immunodeficiency virus prevalence across different districts is inconsistent, with Western areas having a higher prevalence while Southern and Northern regions showed varying trends. Hotspot regions were identified, with changes in high-risk areas over time. Predictors of human immunodeficiency virus prevalence in hotspot areas include age 15–19, urban residents and no formal education. The study suggests the need for prevention and intervention programmes for these high-risk areas and groups to reduce human immunodeficiency virus transmission in Sierra Leone.